Studies on Synthesis and Dyeing Preformance of Acid Dyes Based on 4,7-Dihydroxy-3,8-di-α-naphthylazo-1,10-phenanthroline-2,9-Dione - B. V. Patel; P. H. Dasondi (E-Journal of Chemistry)
Some new azo acid dyes were prepared by coupling various diazotized acid components such as anthranilic acid, sulphanilic acid, laurentacid, peri acid, tobias acid, H-acid, J-acid, gamma acid, sulphotobias acid,4-aminotoluiene-3-sulphonic acid, 5-sulpho- anthranilic acid, 2-naphthylamine-3,6,8-trisulphonic acid, bronner acid, metanilic acid and cleve acid with 4,7-dihydroxy-3,8-di-α-naphthylazo-1,10-phenanthroline-2,9-dione. The dyes were characterized by elemental, IR and TLC analyses. Their dyeing performance as acid dyes has been assessed on viscose rayon, wool and cotton fibres.